Determination of the Most Appropriate Alternative Dispute Resolution Methods for Airport Projects: A Fuzzy VIKOR Approach - Cevikbas, Murat; Okudan, Ozan; Isik, Zeynep (KOREAN SOCIETY OF CIVIL ENGINEERS-KSCE, 2023)
Being prone to dispute, airport projects involve diverse stakeholders including also national and international aviation authorities, and this complicates the dispute resolution process in these projects. Hence, decision-makers should not entirely rely on standard forms of contracts to settle disputes in airport projects. Instead, these projects necessitate a specific dispute resolution framework that meets their needs. Even though some effort has already been devoted to developing a framework for ADR selection, most of these studies neglect airport projects. Furthermore, existing studies fell short of adopting more advanced techniques such as fuzzy set logic and Fuzzy VlseKriterijumska Optimizacija | Kompromisno Resenje (VIKOR), posing a variety of drawbacks. Thus, this study aims to guide decision-makers by developing a selection framework of Alternative Dispute Resolution (ADR) methods to resolve disputes in airport projects. Firstly, the literature was reviewed comprehensively to reveal the criteria affecting the selection of ADR methods. Next, Focus Group Discussion (FGD) session was conducted with the participation of 17 experts who have diverse experiences in the dispute resolution process in airport projects to omit or validate the detected criteria obtained from the literature review. This was then followed by the Fuzzy VIKOR method to evaluate the importance of each ADR method. In the final step, sensitivity analysis was performed to confirm the reliability of the results. The results confirmed that a plethora of factors governs the ADR selection process, pinpointing the need for a systematic and holistic framework. Secondly, the Expert Determination was determined to be the most convenient ADR method for airport projects. The Expert Determination was followed by the Dispute Adjudication Board (DAB) and Arbitration, respectively. Revealing the very first holistic framework concerning ADR selection for airport projects, this study significantly contributes to the dispute resolution domain. Furthermore, this proposed framework is believed to have promising benefits for the decision-makers while drafting the contract clauses in terms of ADR methods in airport projects.
Keywords: ADR; Contract; Dispute; Fuzzy VIKOR; Airport; Construction; CONSTRUCTION PROJECTS; SELECTION; DESIGN; MANAGEMENT; MODEL; Engineering